The associations of transformational leadership and team cohesion on the psychological health of young football players through basic psychological needs - Yildirim, S.; Yildiz, A.; Bozkurt, H. T.; Bilgin, E.; Yüksel, Y.; Koruc, Z. (Science and Medicine in Football, 2024)
The present study examined the associations of transformational leadership behaviors and team cohesion with the psychological health (life satisfaction, positive and negative affect, and burnout) of athletes and the indirect relationship of basic psychological needs. The sample consisted of 252 (boys) players aged between 13 and 15. The model data fit was also verified. The results demonstrated that the transformational leadership behaviors of coaches were indirectly related to athletes` psychological health. Team cohesion was related to athletes` psychological health both directly and indirectly. Basic psychological needs played an indirect role in these relationships. Transformational leadership and team cohesion have important implications for the healthy development of young people.